Metal-Matrix Composites Innovations, Advances and Applications An SMD Symposium in Honor of William C. Harrigan, Jr. (The Minerals, Metals & Materials Series,, 2018)
This book includes papers on recent research carried out in the field of metal-matrix composites (MMCs). Processing, microstructure, and mechanical properties of MMCs and unreinforced matrix alloys will be covered with a focus on aluminum, titanium, nickel, and copper MMCs. Those involved in the research of MMCs and unreinforced alloys, particularly in aerospace, space, and automotive materials research, will find this volume indispensible.